2008
DOI: 10.1177/0011392108095345
|View full text |Cite
|
Sign up to set email alerts
|

Rational Loyalty and Whistleblowing

Abstract: Whistleblowers often pay a heavy price for exposing what they perceive to be organizational wrongdoing. Based on 18 narrative interviews with South African whistleblowers, this article considers the contradictory nature of whistleblowing by exploring the role of loyalty, trust and betrayal in explaining the retaliation that whistleblowers receive. It concludes that whistleblowing can only achieve its aims of addressing organizational wrongdoing without high costs for the whistleblower and the organization if o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…Essentially rational loyalty is a loyalty that the organization and the member share for the organisations' explicit, legitimate set of mission statement, goals, value statement and code of conduct (Vandekerckhove, 2006). So, if organizational loyalty means being loyal to its values and norms (which are validated by the society it operates in because they are public), then observing wrongdoing would compel the employee to blow the whistle (Uys, 2008).…”
Section: Organisations and Whistleblowing Arrangementsmentioning
confidence: 99%
“…Essentially rational loyalty is a loyalty that the organization and the member share for the organisations' explicit, legitimate set of mission statement, goals, value statement and code of conduct (Vandekerckhove, 2006). So, if organizational loyalty means being loyal to its values and norms (which are validated by the society it operates in because they are public), then observing wrongdoing would compel the employee to blow the whistle (Uys, 2008).…”
Section: Organisations and Whistleblowing Arrangementsmentioning
confidence: 99%
“…To distinguish between what is considered normal requirements in such a function and what may be regarded as whistle-blowing, Miethe (1999: 17) argues that, in such cases, the definition of whistle-blowing should be restricted to those who go outside the prescribed channels to disclose the information, as those whistle-blowers who remain internal would not suffer victimisation. However, research has demonstrated that role-prescribed whistle-blowers are often victimised in similar ways to that of the non-role-prescribed whistleblowers (Uys, 2008).…”
Section: Definition Of Conceptsmentioning
confidence: 99%
“…If the patient is not morbidly or mortally affected by the incident, why should the integrity and reputation of a colleague be damaged? Whistle-blowers (or snitches) are traditionally despised in the community [8,9] and for as long as you live or work in the community, fingers will be pointed and tones will be hushed when you are nearby as being the person who ruined Dr XYZ's career. The whole scenario reminds one of the "Omerta" the culture of "silence" by the Cosa Nostra.…”
Section: The Culturementioning
confidence: 99%